Arms export controls, subsidies and the WTO exemption - María del Carmen García-Alonso; Paul Levine (University of Kent, Department of Economics, 2003)
Owing to the WTO exemption that allows governments to subsidise arms exports, the arms trade is one of the few remaining areas of trade where we observe lump-sum and per unit transfers to exports. This paper examines the effect of arms controls, in the form of licensing delays, on the incentives to subsidise arms exports and conversely the effect of the WTO arms trade exemption on the incentives to break arms control agreements. Our main result is that arms controls and free trade commitments re-enforce each other. Licensing delays reduce the incentive to subsidise and free trade without subsidies reduces the benefits of a unilateral abrogation of arms controls. Transparency actually worsens the Nash inefficiencies at play in that incomplete information leads to lower subsidies and lower arms exports.
Keywords: F12; O31; 330; arms export controls; export subsidies; World Trade Organisation; Rüstungsexportkontrolle; Exportsubvention; WTO-Regeln; Theorie